El laberinto de la invisibilidad de los negros en México. - Laurent Lalekou, Kouakou (Humania del Sur: Revista de Estudios Latinoamericanos, Africanos y Asiáticos)
In Mexico there are blacks, but they are not seen, they exist, but they are invisible. Th ey arrived during the colonization playing fundamental roles in the construction of the country. Th ey participated in the conquest, the economic development and the liberating struggles. Juan Garrido introduced wheat in Mexico and was the fi rst to grow it; Gaspar Yanga shouted the cry of American freedom. One came to occupy the Palace of Mexico as president. Th e present study highlights the reasons for the absent presence of blacks in Mexico, their manifestations today and it analyzes how they can get out of the impasse in which they have been locked up.